Overview of the accessibility of webpages, related research, advantages, guidelines and recommendation - Prantner Kvaszingerné, Csilla (Teaching Mathematics and Computer Science, 2018)
The essay aims to provide a survey of web accessibility, introduce the relevant research results along with describing the advantages of obstacle free webpages. Furthermore, I will attempt to promote the awareness of the significance of accessibility and equal access to information in case of educational webpages especially in the higher education sphere. My primary audience are educational policy makers and leaders of higher education institutions along with in-service teachers who regularly use webpages during their daily work with students struggling with various impairments. The article's focus is expanded onto the relevant professional and legal background, the most important accessibility principles in addition to discussing the tools assuring accessibility and the presentation of best practices for web developers elaborating the electronic learning environments for higher education institutions.